Jak nazywały Jana Pawła II media rosyjskojęzyczne - Gorzelana, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In accordance with the purpose set out at the beginning, the publication presents the diversity of ways of referring to Pope John Paul II in the Russian-language media in the last years of his life (1996-2005). Several hundred articles downloaded from the websites of magazines, radio and television broadcasts and other news portals published in Russia and abroad (e.g. "Die Presse", "La Stampa", "The Independent") have served as the material basis for this research. There were two distinct periods of time when materials were collected - the first one in the years immediately after John Paul II`s death (2005-2007), and the second one in 2022-2024. As the result of the foregoing, differences appeared in Internet sources, e.g. regarding the extension or shortening of the title - such changes were marked and commented on.
Keywords: nazwa; oficjalna tytulatura; określenia metaforyczne; Jan Paweł II, papież (1929-2005); media rosyjskojęzyczne; name; official titular; metaphorical terms; John Paul II; Russian-language media